Small and Medium Enterprises (SMEs) and Public Procurement Contracts in Developing Countries - Obanda, Peter W. (Longhorn publishers., 2011)
SMEs are often excluded from public procurement contracts because of administrative requirements for mandatory bidding processes, their inadequate size or capacity to deliver. This is despite the advantages that accrue from their inclusion. In this paper we analytically delineate strategic and management interventions that can enable youth SMEs in Uganda obtain public procurement contracts to maximize sustainability in the context of inclusive growth. Data collected from a questionnaire survey of Municipalities and Town Councils enabled the testing and analysis of the emergent propositions. Using the institutional and systems thinking approaches, they were substantially supported. Implementation of the interventions has cost implications in terms of procurement stakeholder training and restructuring of the information systems. However, given the socio-economic context particularly of high youth unemployment in Uganda they ought to be undertaken. Further research in developing concrete interventions in information systems is critical given that process transformation is a very difficult activity.
Keywords: Small and Medium Enterprises (SMEs); Public Procurement Contracts; Developing Countries